2018
DOI: 10.1016/j.celrep.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Selenof as a Gatekeeper of Secreted Disulfide-Rich Glycoproteins

Abstract: Selenof (15-kDa selenoprotein; Sep15) is an endoplasmic reticulum (ER)-resident thioredoxin-like oxidoreductase that occurs in a complex with UDP-glucose:glycoprotein glucosyltransferase. We found that Selenof deficiency in mice leads to elevated levels of non-functional circulating plasma immunoglobulins and increased secretion of IgM during in vitro splenic B cell differentiation. However, Selenof knockout animals show neither enhanced bacterial killing capacity nor antigen-induced systemic IgM activity, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…A small study in humans showed a positive effect on antibody titers against the diphtheria vaccine with selenium supplementation that correspond to increased lymphocyte counts [ 104 ]. In a more recent study involving Selenoprotein F (SELENOF) knockout mice, elevated levels of immunoglobulins were detected in the sera that were nonfunctional [ 38 ]. The authors of this study concluded that SELENOF functions as a gatekeeper of immunoglobulins in the endoplasmic reticulum (ER), which supports the redox quality control of these proteins and likely other proteins.…”
Section: Leukocyte Functionsmentioning
confidence: 99%
“…A small study in humans showed a positive effect on antibody titers against the diphtheria vaccine with selenium supplementation that correspond to increased lymphocyte counts [ 104 ]. In a more recent study involving Selenoprotein F (SELENOF) knockout mice, elevated levels of immunoglobulins were detected in the sera that were nonfunctional [ 38 ]. The authors of this study concluded that SELENOF functions as a gatekeeper of immunoglobulins in the endoplasmic reticulum (ER), which supports the redox quality control of these proteins and likely other proteins.…”
Section: Leukocyte Functionsmentioning
confidence: 99%
“…In vitro, Sep15 has been shown to increase the enzymatic activity of UGGT1/2 [83]. Sep15 may modulate the selection of substrates by UGGT or act upon substrates modified by UGGT to help with their repair and folding [86]. Selenocysteines, considered the 21 st amino acid, are found in the active site of Sep15.…”
Section: Carbohydrate-dependent Protein Quality Controlmentioning
confidence: 99%
“…These domains of UGGT do not carry a catalytic site, and therefore lack a direct role in disulfide bond formation, but expose hydrophobic stretches for recognition of unfolded glycoproteins [ 58 ]. UGGT associates with a small selenoprotein, Sep15, also called Selenof [ 59 ]. Sep15 contains a catalytically active thioredoxin-like domain, implying that it may have a role in oxidoreductase activity on the glycoprotein substrate.…”
Section: Oxidoreductases Associated With the Glycoprotein Folding mentioning
confidence: 99%
“…The exact function of Sep15 is unknown, but its association with UGGT indicates its possible role in either modulating UGGT enzyme activity or assessing the disulfide bonds of the UGGT substrates. Sep15 knockout mice showed increased levels of secreted non-functional immunoglobulins, suggesting that it might function as a quality control gatekeeper for misfolded glycoproteins [ 59 ].…”
Section: Oxidoreductases Associated With the Glycoprotein Folding mentioning
confidence: 99%